2010
DOI: 10.1007/s00442-010-1718-x
|View full text |Cite
|
Sign up to set email alerts
|

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation

Abstract: Understanding processes underlying spatial distribution of tree species is fundamental to studying species coexistence and diversity. This study modeled point patterns of tree distribution, expressed by Cartesian coordinates of individual trees within a mapped forest stand, for the purpose of identifying processes that may generate spatial patterns of tree communities. We used four primary point pattern processes (homogeneous Poisson process, inhomogeneous Poisson process, homogeneous Thomas process, and inhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 32 publications
(46 reference statements)
6
117
1
Order By: Relevance
“…Interspecific associations gradually change as forests develop, increasing as the trees age, and determining the spatial distribution pattern (Liu et al 2014). Interspecific competition occurs at small scales, and the effect of environmental heterogeneity (resources and space) dominates the distributional patterns of different species (Lin et al 2011;Kang et al 2014). Our analysis showed that negative association between Q. aliena var.…”
Section: Discussionmentioning
confidence: 78%
“…Interspecific associations gradually change as forests develop, increasing as the trees age, and determining the spatial distribution pattern (Liu et al 2014). Interspecific competition occurs at small scales, and the effect of environmental heterogeneity (resources and space) dominates the distributional patterns of different species (Lin et al 2011;Kang et al 2014). Our analysis showed that negative association between Q. aliena var.…”
Section: Discussionmentioning
confidence: 78%
“…For example, cones of coniferous trees are large and heavy; thus, the cones do not disperse far. The seedlings and saplings from these seeds inevitably form aggregated distributions after germination (Seidler and Plotkin, 2006;Tamme et al, 2010;Lin et al, 2011). With Tilia trees, seedlings are typically abundant near the mother tree because of root sprouting (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In order to simulate the spatial autocorrelation structure of species caused by dispersal limitation, a homogeneous Thomas model was employed to simulate the aggregation of species based on observed data (Waagepetersen 2007;Shen et al 2009;Lin et al 2011). These mimicked distributions were used as a null model in the analysis (John et al 2007).…”
Section: Study Sitementioning
confidence: 99%
“…Spatial point process models can mimic the observed spatial structure produced by ecological processes such as dispersal limitation, and can contribute to disentangling the compound effect of habitat association and dispersal limitation in the study of community assembly rules (e.g. Shen et al 2009;Lin et al 2011). Studies of species-environment associations in forest ecosystems are often based on habitat types in term of topographic factors previously Lai et al 2009;Legendre et al 2009).…”
Section: Introductionmentioning
confidence: 99%